Risk of degenerative ankle joint disease in volleyball players: study of former elite athletes - Gross, P.; Marti, B. (International Journal of Sports Medicine, 1999)
To estimate the influence of long-term, high-intensity volleyball playing on premature osteoarthritis (OA) of the ankle joint, we examined a group of 22 former elite volleyball-players age (34 +/- 6 yrs.) who had played for at least 3 years in the highest volleyball league in Switzerland, and 19 normal healthy untrained controls (35 +/- 6 yrs.). Volleyball-athletes had played during an average of 5.5 (+/- 2) h/wk for 8.5 (+/- 3) yrs. Twenty of the 22 players had suffered from at least one ankle sprain (average: 3.5), 10 had had ruptures of the lateral ligaments (8 of them operated). Four players had severe mechanical instability, 5 a talar varus tilt in the stress X-ray of more than 8 degrees. Subchondral sclerosis and osteophytes were more prevalent in volleyballers than in controls (p < 0.001), while the difference in joint space was not significant. No severe grades of OA could be observed in these former elite volleyball players. Yet, a radiologic score of degenerative ankle disease was elevated in 19/22 of them, but only in 2/19 controls (p<0.001). In multiple regression analysis among athletes, the anterior drawer sign and a feeling of instability were the only significant and independent predictors of an increased radiological index (p = 0.003 and p = 0.02, respectively) from an initial set of 9 variables covering career length and intensity as volleyball player, clinical signs of ankle instability and age. Even if in the present study, athletes had clearly more radiologic findings than controls--such as spur formation and subchondral sclerosis--long-term, high-intensity volleyball playing alone could not be confirmed as an independent risk factor for OA of the ankle joint however, a combination of chronic lateral ankle instability with intensive volleyball playing could marginally increase the risk of ankle OA.